Community aspirations and cooperation: Prescriptive vs. descriptive role models - Marcela Ibanez; Menusch Khadjavi; Christina Martini (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2021)
This paper examines the hypothesis that cooperation depends on the aspirations that individuals hold for their community welfare and tests whether videos that depict either a successful example of collective action or living conditions in rural areas can shape community aspirations and increase cooperation among rural communities in Zambia. The results of a lab in the field experiment indicate that compared with the no video condition, unconditional contributions are higher in the video that presents village life while the collective action video does not affect cooperation. When both contributors watch the village life video, conditional contributions are also higher compared to the control treatment. This points to the importance of social norms in the evolution of collective action. We find that individual aspirations are significantly negatively related to the unconditional contribution decision, while community aspirations do not correlate with contribution levels.
Keywords: C92; D70; D91; O12; 330; aspiration; cooperation; role model; public good; social norms; development